On the interchangeability of calcineurine inhibitors - K. E. Zatolochina; R. N. Alyautdin; E. O. Zhuravleva; E. Yu. Pasternak; M. A. Darmostukova; E. Yu. Kolesnikova; B. K. Romanov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Calcineurin inhibitors, cyclosporine and tacrolimus, are the main immunosuppressants used in solid organ transplantation, but the peculiarities of their pharmacokinetics allow to classify them to a group of medicines with a narrow therapeutic range. Currently in Russia more than 10 generic drugs of cyclosporine and tacrolimus are used. In this review the problem of interchangeability of cyclosporine and tacrolimus is discussed. The pharmacokinetic and technological factors that affect the bioequivalence of calcineurin inhibitors are presented.